2019
DOI: 10.1039/c9ta05601g
|View full text |Cite
|
Sign up to set email alerts
|

Neutral-pH overall water splitting catalyzed efficiently by a hollow and porous structured ternary nickel sulfoselenide electrocatalyst

Abstract: A hollow and porous structured nickel sulfoselenide catalyst was developed as a new type of bifunctional electrocatalyst for neutral-pH water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 73 publications
1
41
0
Order By: Relevance
“…It is worth noting that, there is also significant progress reported on OER catalysts that worked at near neutral pH. [33][34][35] However, the overall device performance using the OER catalysts still suffers from some kinetic loss, low ion conduction and transport issues, especially at high current density. In addition, the use of buffer solutions for more neutral pH may cause challenges in an actual device, and nonprecious metal oxides stability at near neutral pH may also be an issue.…”
mentioning
confidence: 99%
“…It is worth noting that, there is also significant progress reported on OER catalysts that worked at near neutral pH. [33][34][35] However, the overall device performance using the OER catalysts still suffers from some kinetic loss, low ion conduction and transport issues, especially at high current density. In addition, the use of buffer solutions for more neutral pH may cause challenges in an actual device, and nonprecious metal oxides stability at near neutral pH may also be an issue.…”
mentioning
confidence: 99%
“…The hollow nanoarchitecture with large specific surface area and void volume was favorable for the infiltration of electrolyte and fast mass/electron transportation, which benefit for the enhanced catalytic performance. [19,39] The energy dispersive X-ray spectroscopy (EDS) elemental mapping images analysis ( Figure 1f) reveals that the Mn, Fe, P, and O elements are distributed homogeneously throughout the whole nanospheres, corroborating the successful doping of Fe. [40] From the inductively coupled plasma optical emission spectrometry (ICP-OES) measurement, we determined the atomic ratio of Fe:Mn to be 1:8.12 (Table S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 84%
“…[15][16][17][18] Specifically, constructing hollow nanostructures especially hollow nanospheres would be beneficial to the increased specific surface area and accelerated charge transfer ability between active sites and intermediates, which is regarded as a feasible route to develop excellent OER catalysts. [19][20][21][22] For example, Wang and coworkers reported the synthesis of lepidocrocite VOOH hollow nanospheres and their good OER activity with overpotential of 270 mV at 10 mA cm −2 . [21] Moreover, it is reported that some amorphous materials exert outstanding catalytic property than their crystalline counterparts, meaning the rational design amorphous catalysts is another attractive method to further promote OER activity.…”
mentioning
confidence: 99%
“…As shown in Figure S16b, the Ir 3 −Ni(OH) 2 /NF∥Ir 3 −Ni(OH) 2 /NF couple delivers the current densities of 10 and 50 mA ⋅ cm −2 at the potentials of 1.54 and 1.76 V in 1 M KOH solution, respectively. Moreover, Ir 3 −Ni(OH) 2 /NF∥Ir 3 −Ni(OH) 2 /NF couple requires a low potential of 1.64 V to afford 10 mA ⋅ cm −2 in 1 M PBS (Figure 4e), which is obviously lower than a string of recently reported neutral‐pH electrocatalysts (Figure 4f) [34–44] . Moreover, Ir 3 −Ni(OH) 2 /NF∥Ir 3 −Ni(OH) 2 /NF shows good stability for water electrolysis under alkaline condition and neutral‐pH water (Figure S14, S15).…”
Section: Resultsmentioning
confidence: 89%
“…Moreover, Ir 3 À Ni(OH) 2 /NF k Ir 3 À Ni(OH) 2 /NF couple requires a low potential of 1.64 V to afford 10 mA • cm À 2 in 1 M PBS (Figure 4e), which is obviously lower than a string of recently reported neutral-pH electrocatalysts (Figure 4f). [34][35][36][37][38][39][40][41][42][43][44] Moreover, Ir 3 À Ni(OH) 2 /NF k Ir 3 À Ni(OH) 2 /NF shows good stability for water electrolysis under alkaline condition and neutral-pH water ( Figure S14, S15).…”
Section: Resultsmentioning
confidence: 99%